PD-L1 expression on tolerogenic APCs is controlled by STAT-3 - Wölfle, Sabine J.; Strebovsky, Julia; Bartz, Holger; Sähr, Aline; Arnold, Caroline; Kaiser, Claus; Dalpke, Alexander; Heeg, Klaus (European journal of immunology, 2011)
During infection, TLR agonists are released and trigger mature as well as differentiating innate immune cells. Early encounter with TLR agonists (R848; LPS) blocks conventional differentiation of CD14+ monocytes into immature dendritic cells (iDCs) resulting in a deviated phenotype. We and others characterized these APCs (TLR-APC) by a retained expression of CD14 and a lack of CD1a. Here, we show in addition, expression of programmed death ligand-1 (PD-L1). TLR-APCs failed to induce T-cell proliferation and furthermore were able to induce CD25+Foxp3+ T regulatory cells (Tregs). Since PD-L1 is described as a key negative regulator and inducer of tolerance, we further analyzed its regulation. PD-L1 expression was regulated in a MAPK/cytokine/STAT-3-dependent manner: high levels of IL-6 and IL-10 that signal via STAT-3 were produced by TLR-APCs. Blocking of STAT-3 activation prevented PD-L1 expression. Moreover, chromatin immunoprecipitation revealed direct binding of STAT-3 to the PD-L1 promoter. Those findings indicate a pivotal role of STAT-3 in regulating PD-L1 expression. MAPKs were indirectly engaged, as blocking of p38 and p44/42 MAPKs decreased IL-6 and IL-10 thus reducing STAT-3 activation and subsequent PD-L1 expression. Hence, during DC differentiation TLR agonists induce a STAT-3-mediated expression of PD-L1 and favor the development of tolerogenic APCs.
First published: 08 December 2010
Gesehen am 05.12.2022